Physicochemical and sensorial characterization of Portuguese bread from Viseu region - Rodrigues, A (2012)
The aim of this study was to characterise the most typical flour mixture bread (wheat flour and rye flour) produced in the Portuguese region of Viseu and evaluate if there are relevant differences between the samples tested. Nine samples from local producers were analysed considering the morphology, physicochemical (density, alveolus percentage, texture, colour and water activity) and sensorial properties. The form and dimensions of all breads were determined, as well as proximate composition and total salt content. The forms of the breads were different, some round and others long. Nutritionally this type of bread turned out to be a food with high nutritional value, high percentage of ash (2.8-4.9%) and low values of fat, with a high range of salt content (0.4-1.4%). The physical properties were quite different between samples, although some of them are not perceptible by the consumer. This was the case of bread density whose results were 0.25-0.56 and the sensorial panel, constituted by a panel of 40 untrained tasters aged 7 to 63 years, did not find any difference. The traditional breads presented overall appreciation between 4.8 and 6.8, related with different colour and elasticity parameters.